Implementasi Model Pembelajaran Discovery Learning pada Materi Sistem Gerak pada Tumbuhan di Kelas VIII SMP Negeri 5 Metro - Budiarti, Budiarti (Al Jahiz, 2023)
Following studyingprocess is tedious for a lot of students, when it is not bemanaged properly and professionally. Therefore, a teacher is required to design and plan the studying program in a systematic, varietive and innovative way.. Through Classroom Action Research, for Class VIII.5 Science’s teacher in the material "Plants Movement System" have tried to apply the model of discovery learning. After carrying out the treatment in 2 cycles, it is proven that the learning outcomes and student motivation have increased quite significantly. This can be proven where based on the results of the pre-test only 18,75% of students who complete with a Minimum Mastery Creteria (MMC) of 72. After treatment in the first cycle and post-test 1, the student's learning completeness increased to 50%. Furthermore, after the treatment was carried out in the second cycle, based on the results of post test 2 it was found that 84,38%of students were declared complete in mastering the material "Plants Movement System". Thiscondition proves that the use of the discovery learningmodel is quite effective in increasing students’ learning result and can help to foster students’ enthusiasm and motivation for following the science learningprocess.